Attributes of information systems design leading to user satisfaction – a banking case study - Padinha, Bruno Miguel Mateus (2015)
With the growing, pervasive use of information systems (IS) by most organizations, particularly companies in technology-intensive businesses such as banking, questions arise as to the effective success of those systems, how to measure it and, most of all, what influences it. User satisfaction, even if not an end goal of IS organizations, is frequently used as a measure of that success and it has been empirically shown to correlate with other more direct measures. Several research lines, then, look at what influences user satisfaction, particularly what characteristics of information systems and their development processes tend to result in higher user satisfaction. The research reported here looks at the specific case study of a Portuguese bank, for which a comprehensive survey is undertaken yearly to record the satisfaction of its thousands of IS users’ regarding its numerous information systems. Additional primary data was collected to characterize the information systems and their development processes, which, once structured and standardized alongside the user satisfaction survey results provided the basis for a quantitative analysis of the relationships between IS success, measured by user satisfaction, and its antecedents, using correlation and multiple linear regression techniques. The significant relationships are analyzed and the conceptual model’s results discussed in light of prior theory on the subject. Several implications for the practice and research communities are finally identified.